Soft skills development in bioengineering students through problem-based learning: An analysis of educational impact (LACCEI, 2024)
This study aimed to evaluate the perception and self-assessment of soft skills development among bioengineering students using problem-based learning (PBL) methodology. A survey was conducted to assess the relevance perception and self-assessment of seven soft skills with different attributes, before and after the PBL course. The study found that bioengineering students recognized the importance of developing soft skills alongside technical expertise. Communication, critical thinking and problem-solving, entrepreneurship, ethics and professional moral, leadership, continuous learning and information handling, and teamwork skills were consistently improved with the PBL course. The PBL methodology had a positive impact on the development of soft skills attributes, as students either improved or maintained their skill levels. However, significant differences were observed in five of the seven soft skills attributes. The use of technology for making presentations and the impact of understanding the external factors were the least developed attributes among students. The study suggests that PBL may not have included enough opportunities for students to develop these skills, and specific activities may need to be incorporated in the future. Overall, the results underscore the importance of integrating soft skills development into bioengineering education and training programs, as these skills are crucial for success in the field.